UK trained osteopaths' relationship to evidence based practice - An analysis of influencing factors. (September 2018) - Weber, Valentin; Rajendran, Dévan
Abstract: Background: Use of evidence based practice (EBP) remains controversial amongst UK osteopaths and developing an understanding of factors that influence EBP implementation is important for the profession. This study aimed to explore factors that influence the use of EBP amongst UK osteopaths and to compare these with other healthcare professionals. Design: We used the JQ37 questionnaire to survey UK registered osteopaths (n = 2010). Logistic regression analyses measured associations between attitudes/beliefs, education, knowledge, EBP skills, and clinical guideline access with osteopaths' age, years since graduation, undergraduate and postgraduate degree level, attention to literature, and use of clinical guidelines. Results: 370 respondents (18.4%) completed the questionnaire: UK osteopaths generally had positive attitudes about EBP. They agreed that EBP was necessary, improved quality of care and assisted clinical decision-making. They also agreed that literature/research findings were useful in their practice and were interested in learning/improving EBP skills necessary to incorporate EBP into practice. Critical appraisal, professional database use, training and familiarity with search strategies were positively associated with younger osteopaths and those with higher levels of degree, or held a research or educational position in addition to clinical practice. Perceived barriers to utilising EBP were lack of time, inapplicability and uniqueness of their osteopathic patient population. Discussion and conclusion: Generally UK osteopaths had positive attitudes about EBP and interested in improving skills needed to implement EBP into practice. However, respondents did not search or use available online practice guidelines, believing guidelines were inapplicable to osteopathic patients, who were unique. Highlights: The majority of osteopaths we surveyed displayed positive attitudes towards EBP. Level of degree and years since graduation impacts on osteopaths' adoption of EBP. Most osteopaths are guideline aware but only a minority utilise these in practice. The greatest barrier to osteopaths using EBP in practice was perceived lack of time.